Pathological Q wave as an indicator of left ventricular ejection fraction in acute myocardial infarction (Medical Journal of Indonesia, 2016)
Background: Q-wave myocardial infarction (QMI) has higher mortality and lower myocardial viability than non-Q-wave myocardial infarction (NQMI), suggesting the existence of pathological Q waves reflects the worse ventricular function. The aim of the study is to determine difference in left ventricular ejection fraction (LVEF) between QMI and NQMI. Methods: The study design was cross-sectional analysis conducted in patients with AMI that were hospitalized and undergone echocardiography in Abdul Wahab Sjahranie County General Hospital Samarinda during February 2014 to March 2015. Standard 12-lead electrocardiograms (ECG) were recorded at presentation, 1 day and 2 days after the onset of AMI as well as using the classical criteria for pathological Q wave. LVEF assessment was performed using echocardiography after the second day since the onset of AMI. Independent-T test was used to determine difference in LVEF using PSPPIRE 0.8.4. Results: There were 34 subjects comprising 16 QMI patients and 18 NQMI patients. QMI had a lower LVEF (42±13%) compared to NQMI (60±11%, p<0.001). The presence of pathological Q waves was associated with LVEF ≤40% (p=0.002). Conclusion: QMI had a lower LVEF than NQMI, provides information about the role of pathological Q wave as an indicator of LVEF.